Attenuation of voltage sags effects and dynamic performance improvement of a multi-motor system - Bensaid Mounir; Abdellfattah Ba-Razzouk; Mustapha Elharoussi; Bouchaib Rached (Institute of Advanced Engineering and Science, 2022)
In many continuous manufacturing processes such as paper, textile, winding and plastic extrusion, electric drives are frequently required to work in synchronization, often with high tolerances to ensure uniform product quality and avoid failure of the product. In a multi-motor system (MMS), voltage dips are the most common cause of the motor stoppage, and the transient loss of synchronism between motors can result in a complete system shutdown. This paper proposes a multi-motor system controlled by a Backstepping strategy to ensure servo-control and synchronization of induction motors. This technique includes indirect rotor field-oriented control (IRFOC), linear speed control, and mechanical tension control, of induction motors. Investigations of symmetrical voltage sag effects on speed, torque, and mechanical tension are also carried out. Simulation results obtained using Matlab®/SimulinkTM/SimPowerSystems® are presented to demonstrate the efficiency of the proposed control strategy.